The dual face of microglia (M1/M2) as a potential target in the protective effect of nutraceuticals against neurodegenerative diseases - Darwish, Samar F.; Elbadry, Abdullah M. M.; Elbokhomy, Amir S.; Salama, Ghidaa A.; Salama, Rania M. (Frontiers in Aging, 2023)
The pathophysiology of different neurodegenerative illnesses is significantly influenced by the polarization regulation of microglia and macrophages. Traditional classifications of macrophage phenotypes include the pro-inflammatory M1 and the anti-inflammatory M2 phenotypes. Numerous studies demonstrated dynamic non-coding RNA modifications, which are catalyzed by microglia-induced neuroinflammation. Different nutraceuticals focus on the polarization of M1/M2 phenotypes of microglia and macrophages, offering a potent defense against neurodegeneration. Caeminaxin A, curcumin, aromatic-turmerone, myricetin, aurantiamide, 3,6′-disinapoylsucrose, and resveratrol reduced M1 microglial inflammatory markers while increased M2 indicators in Alzheimer's disease. Amyloid beta-induced microglial M1 activation was suppressed by andrographolide, sulforaphane, triptolide, xanthoceraside, piperlongumine, and novel plant extracts which also prevented microglia-mediated necroptosis and apoptosis. Asarone, galangin, baicalein, and α-mangostin reduced oxidative stress and pro-inflammatory cytokines, such as interleukin (IL)-1, IL-6, and tumor necrosis factor-alpha in M1-activated microglia in Parkinson's disease. Additionally, myrcene, icariin, and tenuigenin prevented the nod-like receptor family pyrin domain-containing 3 inflammasome and microglial neurotoxicity, while α-cyperone, citronellol, nobiletin, and taurine prevented NADPH oxidase 2 and nuclear factor kappa B activation. Furthermore, other nutraceuticals like plantamajoside, swertiamarin, urolithin A, kurarinone, Daphne genkwa flower, and Boswellia serrata extracts showed promising neuroprotection in treating Parkinson’s disease. In Huntington's disease, elderberry, curcumin, iresine celosia, Schisandra chinensis, gintonin, and pomiferin showed promising results against microglial activation and improved patient symptoms. Meanwhile, linolenic acid, resveratrol, Huperzia serrata, icariin, and baicalein protected against activated macrophages and microglia in experimental autoimmune encephalomyelitis and multiple sclerosis. Additionally, emodin, esters of gallic and rosmarinic acids, Agathisflavone, and sinomenine offered promising multiple sclerosis treatments. This review highlights the therapeutic potential of using nutraceuticals to treat neurodegenerative diseases involving microglial-related pathways.